Morphologies in‐between: The impact of the first steps on the human talus. Issue 1 (21st June 2022) - Figus, Carla; Stephens, Nicholas B.; Sorrentino, Rita; Bortolini, Eugenio; Arrighi, Simona; Higgins, Owen A.; Lugli, Federico; Marciani, Giulia; Oxilia, Gregorio; Romandini, Matteo; Silvestrini, Sara; Baruffaldi, Fabio; et al.
Abstract: Objective: The development of bipedalism is a very complex activity that contributes to shaping the anatomy of the foot. The talus, which starts ossifying in utero, may account for the developing stages from the late gestational phase onwards. Here, we explore the early development of the talus in both its internal and external morphology to broaden the knowledge of the anatomical changes that occur during early development. Materials and Methods: The sample consists of high‐resolution microCT scans of 28 modern juvenile tali (from 36 prenatal weeks to 2 years), from a broad chronological range from the Late Roman period to the 20th century. We applied geometric morphometric and whole‐bone trabecular analysis to investigate the early talar morphological changes. Results: In the youngest group (<6 postnatal months), the immature external shell is accompanied by an isotropic internal structure, with thin and densely packed trabeculae. After the initial attempts of locomotion, bone volume fraction decreases, while anisotropy and trabecular thickness increase. These internal changes correspond to the maturation of the external shell, which is now more defined and shows the development of the articular surfaces. Discussion: The internal and external morphology of the human talus reflects the diverse load on the foot during the initial phases of the bipedal locomotion, with the youngest group potentially reflecting the lack of readiness of the human talus to bear forces and perform bipedal walking. These results highlight the link between mechanical loading and bone development in the human talus during the acquisition of bipedalism, providing new insight into the early phases of talar development.